Influence of pregnancy and puerperium in the leucogram of Saanen goats (Capra hircus), bred in the state of São Paulo - Viana, Rinaldo Batista; Birgel Junior, Eduardo Harry; Ayres, Maria Consuelo Caribé; Biojoni, Fernanda de Souza Meirelles; Souza, Maria do Carmo Custódio de; Birgel, Eduardo Harry (Brazilian Journal of Veterinary Research and Animal Science, 2002)
With the intention of evaluating the influence of pregnancy and puerperium in the leucogram of Saanen goats (Capra hircus), blood samples were taken from 150 goats bred on the State of São Paulo and were allotted into 5 experimental groups of 30 goats each as described: non-pregnant; initial pregnancy (30 to 60 days of pregnancy); middle pregnancy (60 to 120 days of pregnancy); late pregnancy (more than 120 days of pregnancy); kidding goats (until 30 days after parturition). The blood samples were collected with EDTA and submitted to the following tests: total leukocyte counts (in the modified Neubauer hemocytometer, using Thoma's liquid as a dilute); and differential leukocyte count (made up with blood smears and stained with Rosenfeld method). The influence of pregnancy and puerperium on the leucogram was verified due to a gradual decrease on the number of leucocytes further on in pregnancy, reaching its lower values at the end of pregnancy and puerperium. This decrease occurred due to behavior observed on the absolute number of lymphocytes that also decreased further on in pregnancy. Therefore the leucograma became mostly neutrophilic at the end of pregnancy and puerperium.